Alat Pendeteksi Kebocoran Gas LPG Pada Resto Ayam Bakar dan Goreng Kremes Tata Berbasis Internet Of Things - Tri Endah Purnamawati; Afu Ichsan Pradana; Joni Maulindar (Universitas Islam Raden Rahmat, Malang, 2024)
LPG (Liquefied Petroleum gas) is one of the most commonly used gases for household purposes, comprising two components: propane (C3H8) and butane (C4H10). However, LPG gas has a drawback, namely the danger associated with gas leaks. LPG gas leaks pose a highly hazardous risk that can impact human safety and the surrounding environment. In this journal, the author discusses the development of a system for monitoring the detection of LPG gas leaks using an MQ-2 sensor and the ESP32 microcontroller. Subsequently, the system transmits LPG gas data to the Blynk application, providing users with quick information through sound and messages. The research test results indicate that the MQ-2 sensor is effective in rapidly detecting gas concentrations ranging from 300 to 1000 ppm.